Certain aspects of premature aging of the immune system at prolonged light stress. - Sorokina, I. V.; Bocharova, T. V. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. There are a number of critical factors that can trigger premature aging of the organism. The neuroendocrine system plays a central role in the regulation of this process. It is known that the all-day illumination is a stress factor which leads to hypopinealism. So we cannot exclude the possibility of negative influence of the prolonged light on the immune system. Objective. Structural-functional peculiarities of the spleen, thymus and bone marrow under prolonged all-day illumination experiment on rabbits. Methods. Experimental animals were exposed to different light modes. Control animals were kept in natural day and night lighting conditions. Experimental rabbits were in artificial lighting in the day and electric lighting in the night during 12 months. Results. Histological study of the thymus revealed decreasing of the number and size of the lobules, reduction of the epithelial components, large areas of sclerosis and lipomatosis. The cell density was statistically decreased in the cortex and in the medullar part. Microscopy of the spleen revealed hypoplasia of the white pulp, reduction in the size and number of lymphoid follicles, thickening of the capsule and trabeculae. The cell density was decreased in T-zone more than in B-zone. An intensified formation of the connective tissue, an increasing of involutive processes and degenerative changes of lymphocytes were found in the spleen and the thymus. The cell density in the bone marrow was decreased too. Conclusion. The decrease in density of cells in combination with involute, dystrophic and sclerotic processes evidence premature age-related changes in central and peripheral organs of the immune system.